Spatial ecology of the Neisseriaceae family in the human oral cavity - Jonathan J. Giacomini; Julian Torres-Morales; Floyd E. Dewhirst; Gary G. Borisy; Jessica L. Mark Welch (Microbiology Spectrum)
ABSTRACT The human oral microbiome is a diverse ecosystem in which bacterial species have evolved to occupy specific niches within the oral cavity. The Neisseriaceae family, which includes human oral species in the genera Neisseria, Eikenella, Kingella, and Simonsiella, plays a significant role in both commensal and pathogenic relationships. In this study, we investigate the distribution and functional adaptations of Neisseriaceae species across oral habitats, focusing on their site tropisms and ecological roles. We employed a metapangenomic approach in which a curated set of reference genomes representing Neisseriaceae diversity was used for competitive mapping of metagenomic reads. Our analysis revealed distinct habitat preferences among Neisseriaceae species, with Kingella oralis, Neisseria elongata, and Neisseria mucosa primarily found in dental plaque; Neisseria subflava on the tongue dorsum; and Neisseria cinerea in the keratinized gingiva. Functional enrichment analyses identified genes and pathways underpinning habitat-specific adaptations. Plaque specialists showed metabolic versatility, with adaptations in nitrogen metabolism, including nitrate reduction and denitrification, lysine degradation, and galactose metabolism. Tongue dorsum specialists exhibited adaptations including enhanced capabilities for amino acid biosynthesis, short-chain fatty acid and glycerol transport, as well as lipopolysaccharide glycosylation, which may aid in resisting antimicrobial peptides and maintaining membrane integrity. These findings provide insights into the ecological roles and adaptive strategies of Neisseriaceae species within the human oral microbiome and establish a foundation for exploring functional specialization and microbial interactions in these niches.IMPORTANCEUnraveling the distribution and functional adaptations of Neisseriaceae within the human oral microbiome is essential for understanding the roles of these abundant and prevalent commensals in both health and disease. Through a metapangenomic approach, we uncovered distinct habitat preferences of various Neisseriaceae taxa across the oral cavity and identified key genetic traits that may drive their habitat specialization and role in host-microbe interactions. These insights enhance our understanding of the microbial dynamics that shape oral microbial ecology, offering potential pathways for advancing oral health research.